Cellular Fragments in the Perivitelline Space Are Not a Predictor of Expanded Blastocyst Quality - Yu, Bo; van Tol, Helena T. A.; Stout, Tom A. E.; Roelen, Bernard A. J. (Frontiers in Cell and Developmental Biology, 2021)
The presence of cellular fragments in the perivitelline space is a commonly used parameter to determine quality before transfer of in vitro produced (IVP) embryos. However, this parameter is difficult to assess after blastocyst expansion. In this study, we used mechanical hatching to confirm the presence of cellular fragments in the perivitelline space of day 9 bovine IVP blastocysts. We further looked for associations between apoptosis within extruded cells/ cellular fragments and the quality of bovine blastocysts using quantitative RT-PCR and immunofluorescence. Surprisingly, more than 42% of expanded blastocysts had cellular fragments in the perivitelline space; however, more than 37% of extruded cells were TUNEL negative. We observed no significant difference in embryo quality between expanded blastocysts with and without cellular fragments in the perivitelline space. Overall, our data suggest that embryos extrude abnormal cells to maintain the developmental potential. The presence of fragmented cells is not an indicator of embryo quality.